Transformasi Masyarakat Miskin Menjadi Entrepneur Melalui Kolaborasi - Yanuar, Yanuar (Jurnal Manajemen, 2011)
The poverty is one of the critical problems that a nation has because it will decrease the citizen living such as bad condition of their health, lack of nutrition, low level of ecucation, les productivity which affects on the national productivity.